2016
DOI: 10.1080/09537287.2016.1193911
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain configuration conundrum: how does the pharmaceutical industry mitigate disturbance factors?

Abstract: How a supply chain (SC) is configured can have a significant impact on the performance of global firms. More specifically, disturbance factors (i.e. those factors associated with uncertainty and risk) are increasingly important considerations. This paper focuses on endogenous, exogenous and environment-related SC disturbance factors and their relative importance when configuring global SCs. Three alternative scenarios of SC configurations for European-based pharmaceutical firms are identified -insource nearsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 58 publications
(88 reference statements)
1
59
0
Order By: Relevance
“…We also construct four key location-related (external) contextual factorsgovernment policy, national human resources, infrastructure and transport and national cultural -and operationalise it. Our findings are concurrent with the limited number of studies which explored partially the outsourced-to country contextual factors and concluded that several uncertainties of outsourcing relationships can be assigned to one or more of these factors and hence can cast a major shadow on the future of the outsourcing relationship (Tjader, Shang, and Vargas 2010, Handley and Angst 2015, Huq, Pawar, and Rogers 2016, Kaur, Singh, and Majumdar 2018. For example, our case study research shows that the strength of outsourced-to country's legal system is very crucial for the flow of knowledge between outsourcing partners.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We also construct four key location-related (external) contextual factorsgovernment policy, national human resources, infrastructure and transport and national cultural -and operationalise it. Our findings are concurrent with the limited number of studies which explored partially the outsourced-to country contextual factors and concluded that several uncertainties of outsourcing relationships can be assigned to one or more of these factors and hence can cast a major shadow on the future of the outsourcing relationship (Tjader, Shang, and Vargas 2010, Handley and Angst 2015, Huq, Pawar, and Rogers 2016, Kaur, Singh, and Majumdar 2018. For example, our case study research shows that the strength of outsourced-to country's legal system is very crucial for the flow of knowledge between outsourcing partners.…”
Section: Discussionsupporting
confidence: 80%
“…The outsourcing research widely demonstrated through comparative studies for different countries that government policies such as free trade policies, foreign investment regulations and the strength of legal system are strong indicators of how attractive or risky a country is as an outsourcing destination Fynes 2013, Bals, Kirchoff, andFoerstl 2016). Additionally, availability of highly skilled and educated human resources and transport and communication infrastructures are proven to be among strong determinants of manufacturing outsourcing location decisions (Kedia and Mukherjee 2009, Lewin, Massani, and Peeters 2009, Huq, Pawar, and Rogers 2016. Lastly, the outsourcing research exhibits that divergence of national cultures poses major challenges to the outsourcing performance through low familiarity and high outsourcees behavioural uncertainty (Tjader, Shang, andVargas 2010, Handley andAngst 2015).…”
Section: Contextual External Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early 20th century, to lower their R&D, manufacturing, and logistics costs and expand access to external resources (Stentoft et al., ), leading pharmaceutical companies, such as Pfizer, Johnson & Johnson, and GSK, started to focus on their core competencies and relocate their noncore SC components to low‐cost locations (Huq et al., ). They employed outsourcing strategies that further globalized the pharmaceutical SCs and significantly increased their competitiveness and profitability (Huq et al., ). At the same time, SC complexity and risk have been magnified and new challenges toward SC coordination (e.g., endogenous, exogenous, and environmental disturbance factors) have been created (Huq et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…They employed outsourcing strategies that further globalized the pharmaceutical SCs and significantly increased their competitiveness and profitability (Huq et al., ). At the same time, SC complexity and risk have been magnified and new challenges toward SC coordination (e.g., endogenous, exogenous, and environmental disturbance factors) have been created (Huq et al., ). After experiencing severe disruptions and dealing with several strategic and operational issues (Asian and Nie, ), these companies decided to reconfigure their SC network using SC localization as a strategic mitigation strategy.…”
Section: Introductionmentioning
confidence: 99%